İLKÖĞRETİM BİRİNCİ KADEME DÜZEYİNDE ÇEVRE İÇERİKLİ DERS KAZANIMLARININ DİSİPLİNLER ARASI YAKLAŞIM AÇISINDAN İNCELENMESİ - Arefe YURTTAŞ>; Eda Erdaş Kartal; Atila Çağlar (OpenAlex, 2020)
Propósito: El medio ambiente es un campo de investigación interdisciplinario relacionado con muchos campos sociales, culturales, psicológicos, económicos y sociales. Por lo tanto, el éxito de un estudio a planificar en educación ambiental requiere dirigir el estudio considerando estas disciplinas. Dado que el medio ambiente y los problemas ambientales afectan a muchas áreas de nuestras vidas, la educación ambiental en los programas de educación debe abordarse con un enfoque interdisciplinario. En la investigación, se examinaron las ganancias relacionadas con el medio ambiente en el plan de estudios de educación primaria en el contexto de la asociación con otras disciplinas basadas en la interdisciplinariedad integrada approach.Design/Methodology/Approach: El estudio es una investigación cualitativa y se utilizó el método de análisis de documentos en el análisis de los datos. Hallazgos: Se determinó que el número de ganancias relacionadas con el medio ambiente en el nivel primario era de 96. Se ha determinado que las ganancias relacionadas con el medio ambiente en el plan de estudios de educación primaria se concentran en algunos cursos como Ciencias de la Vida, Ciencias y Estudios Sociales, y estas ganancias no se incluyen en el plan de estudios de algunos cursos. Se ha observado que el nivel de asociación de las ganancias determinadas con otras disciplinas es débil. Además, no se ha encontrado una explicación clara en el plan de estudios sobre la necesidad de manejar los logros relacionados con el medio ambiente con un enfoque interdisciplinario. Aspectos destacados: La investigación muestra que los logros ambientales en el plan de estudios de educación primaria son insuficientes en términos de enfoque interdisciplinario integrado.

Objectif : L'environnement est un domaine de recherche interdisciplinaire lié à de nombreux domaines sociaux, culturels, psychologiques, économiques et sociaux. Par conséquent, la réussite d'une étude à planifier en éducation à l'environnement nécessite de diriger l'étude en considérant ces disciplines. Étant donné que les problèmes environnementaux et environnementaux affectent de nombreux domaines de notre vie, l'éducation environnementale dans les programmes d'éducation devrait être traitée avec une approche interdisciplinaire. Dans la recherche, les gains liés à l'environnement dans le programme d'enseignement primaire ont été examinés dans le contexte de l'association avec d'autres disciplines basées sur l'interdisciplinarité intégrée approach.Design/Methodology/Approach : L'étude est une recherche qualitative et une méthode d'analyse de documents a été utilisée dans l'analyse des données. Conclusions : Le nombre de gains liés à l'environnement au niveau primaire a été déterminé à 96. Il a été déterminé que les gains liés à l'environnement dans le programme d'enseignement primaire sont concentrés dans certains cours tels que les sciences de la vie, les sciences et les études sociales, et ces gains ne sont pas inclus dans le programme de certains cours. Il a été observé que le niveau d'association des gains déterminés avec d'autres disciplines est faible. En outre, aucune explication claire n'a été trouvée dans le programme sur la nécessité de gérer les gains liés à l'environnement avec une approche interdisciplinaire. Points saillants : La recherche montre que les gains environnementaux dans le programme d'enseignement primaire sont insuffisants en termes d'approche interdisciplinaire intégrée.

Purpose: Environment is an interdisciplinary research field related to many social, cultural, psychological, economic and social fields. Therefore, the success of a study to be planned in environmental education requires directing the study by considering these disciplines. Since environment and environmental problems affect many areas in our lives, environmental education in education programs should be handled with an interdisciplinary approach. In the research, environmental related gains in primary education curriculum were examined in the context of associating with other disciplines based on integrated interdisciplinary approach.Design/Methodology/Approach: The study is qualitative research and document analysis method was used in the analysis of the data.Findings: The number of environmental related gains at primary level was determined to be 96. It has been determined that the environmental related gains in primary education curriculum are concentrated in some courses such as Life Science, Science and Social Studies, and these gains are not included in the curriculum of some courses. It has been observed that the level of association of the determined gains with other disciplines is weak. In addition, no clear explanation has been found in the curriculum about the necessity of handling environmental related gains with an interdisciplinary approach. Highlights: The research shows that environmental gains in primary education curriculum are insufficient in terms of integrated interdisciplinary approach.

Purpose: Environment is an interdisciplinary research field related to many social, cultural, psychological, economic and social fields. Therefore, the success of a study to be planned in environmental education requires directing the study by considering these disciplines. Since environment and environmental problems affect many areas in our lives, environmental education in education programs should be handled with an interdisciplinary approach. In the research, environmental related gains in primary education curriculum were examined in the context of associating with other disciplines based on integrated interdisciplinary approach.Design/Methodology/Approach: The study is qualitative research and document analysis method was used in the analysis of the data.Findings: The number of environmental related gains at primary level was determined to be 96. It has been determined that the environmental related gains in primary education curriculum are concentrated in some courses such as Life Science, Science and Social Studies, and these gains are not included in the curriculum of some courses. It has been observed that the level of association of the determined gains with other disciplines is weak. In addition, no clear explanation has been found in the curriculum about the necessity of handling environmental related gains with an interdisciplinary approach.Highlights: The research shows that environmental gains in primary education curriculum are insufficient in terms of integrated interdisciplinary approach.

الغرض: البيئة هي مجال بحثي متعدد التخصصات يتعلق بالعديد من المجالات الاجتماعية والثقافية والنفسية والاقتصادية والاجتماعية. لذلك، فإن نجاح الدراسة التي سيتم التخطيط لها في التربية البيئية يتطلب توجيه الدراسة من خلال النظر في هذه التخصصات. نظرًا لأن البيئة والمشاكل البيئية تؤثر على العديد من المجالات في حياتنا، يجب التعامل مع التعليم البيئي في برامج التعليم بنهج متعدد التخصصات. في البحث، تم فحص المكاسب المتعلقة بالبيئة في مناهج التعليم الابتدائي في سياق الارتباط بالتخصصات الأخرى بناءً على approach.Design/Methodology/Approach المتكامل متعدد التخصصات: الدراسة عبارة عن بحث نوعي وتم استخدام طريقة تحليل المستندات في تحليل البيانات. النتائج: تم تحديد عدد المكاسب المتعلقة بالبيئة في المستوى الابتدائي على أنه 96. وقد تقرر أن المكاسب المتعلقة بالبيئة في مناهج التعليم الابتدائي تتركز في بعض المقررات مثل علوم الحياة والعلوم والدراسات الاجتماعية، ولا يتم تضمين هذه المكاسب في مناهج بعض المقررات. وقد لوحظ أن مستوى ارتباط المكاسب المحددة بالتخصصات الأخرى ضعيف. بالإضافة إلى ذلك، لم يتم العثور على تفسير واضح في المناهج الدراسية حول ضرورة التعامل مع المكاسب البيئية ذات الصلة بنهج متعدد التخصصات. النقاط الرئيسية: يظهر البحث أن المكاسب البيئية في مناهج التعليم الابتدائي غير كافية من حيث النهج المتكامل متعدد التخصصات.
Keywords: Eğitim Üzerine Çalışmalar; Studies on Education; Social Sciences; Sustainability Education in Higher Education Institutions; Curriculum Implementation; Management, Monitoring, Policy and Law; Environmental education; Education; Character Education in Schools and Teacher Training; Context (archaeology); Sociology; Psychology; Sustainability Education; Environmental education; Interdisciplinary approach; Primary education Education; Curriculum; Factors Influencing Pro-environmental Behavior; Geography; Pedagogy; Social science; Mathematics education; FOS: Sociology; FOS: Psychology; Environmental Attitudes; Social environment; Archaeology; Pro-environmental Behavior; Environmental Education; Environmental Science; Physical Sciences; Curriculum; çevre eğitimi; disiplinler arası yaklaşım; ilköğretim; eğitim; öğretim programı; 11. Sustainability; 10. No inequality; 4. Education; 13. Climate action